An Evaluation of Fetal Heart Rate Characteristics Associated With Neonatal Encephalopathy: A Case-Control Study. Issue 3 (March 2019) - Frey, H. A.; Liu, X.; Lynch, C. D.; Musindi, W.; Samuels, P.; Rood, K. M.; Thung, S. F.; Bakk, J. M.; Cheng, W.; Landon, M. B.
Abstract : (Abstracted from BJOG 2018;125:1480–1487) Neonatal encephalopathy is a clinical condition identified shortly after birth in term or near-term infants that is characterized by abnormal neurological function. Affected infants often present with a decreased level of consciousness or seizures, as well as difficulty initiating and maintaining respirations and abnormal reflexes or tone.